Relações de poder e recrutamento militar na Paraíba durante a guerra do Paraguai (1864-1870) - Rabelo, Juliana Dantas (2017)
This study analyses the military recruitment in Paraíba for the Paraguay War (1864-1870) in the light of the political clashes in the Province. At the beginning of 1865, the Imperial government demanded of the Province’s Presidents agility in the meeting of contingents that could integrate the military forces in operation in the South of the country. The Empire’s National Guard was summoned, the enlistment of volunteers was encouraged and the recruitment, authorized. From that moment, as representatives of the central government in the Provinces, the Presidents had the duty to collaborate with him. However, the opposition of private power and the resistance of the free population to military recruitment hampered this task. The former, dissatisfied with the intervention of the central government in local affairs, which interfered in consolidated clientelistics relations, put a number of obstacles in the way of recruitment in the Province. On the other hand, fearing to be sent to the war, the target population of this recruitment opted for different strategies to escape from the authorities. The military mobilization in Paraíba was the subject of discussions waged by local political newspapers, such as Tempo (conservative) and Publicador (liberal). Therefore, these newspapers have become the main source used by us in this work, along with the Provincial Presidential Reports, official correspondences, among others. With the contributions of the New Military History, we tried to elucidate a little more about the daily life of Paraíba during the years of the Paraguay War.